Digital Press In The Era Of Disruption: Reconstructing The Legal Framework Toward Responsible Freedom Of Information In Indonesia - Lukman, Dian Arlesti; Djatmika, Prija; Sugiri, Bambang; Yuliati, Yuliati (Universitas Islam kadiri, 2026)
The era of digital technological disruption has structurally altered the press ecosystem in Indonesia. The presence of media entities operating online without established institutional infrastructure — academically termed